Nitric oxide levels in response to the patients with different stage of diabetes - Ozcelik, O.; Algul, S. (C M B Assoc, 2017)
The association between hyperglycaemia and serum nitric oxide (NO) levels has not yet been fully clarified. Thus, it was aimed to evaluate the concentration of NO metabolites (nitrate, nitrite) in diabetic patients and to find the relationship between hyperglycaemia and serum NO levels in diabetic and prediabetic patients, and control groups. In this study, 100 subjects were divided into 3 groups: healthy control (n=20), prediabetic (n=40) and diabetic (n=40). Glycemic control was assessed using glycated hemoglobin (HbA1c). Nitrate and nitrite levels were measured using the Griess reagent. NO was obtained from the sum of nitrates and nitrites. The serum NO level was higher in diabetic (53.4 +/- 2.0 mu M) and prediabetic patients (51.6 +/- 1.6 mu M) as compared to that in the control (45.6 +/- 1.2 mu M), (p< 0.05). The NO level was not significantly different in diabetic and prediabetic patients. Higher levels of serum glucose, insulin and HOMA-IR may be responsible for the activation of endothelial cells to increase NO levels. This study supports the role of insulin resistance in increased NO levels in both diabetic and prediabetic patients.
Keywords: Nitric oxide; Diabetes; Prediabetes; Hyperglycaemia; Endothelial dysfunction